2012
DOI: 10.7598/cst2012.184
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterizaton of Some N-Mannich Bases as Potential Antimicrobial, Anthelmintic and Insecticidal Agents

Abstract: A series of N-Mannich bases of benzimidazolyl substituted 1H-isoindole-1,3(2H) dione have been derived by the reaction of different substituted amino acids with phthalic anhydride to yield 2-(substituted) 1H-isoindole-1,3(2H) diones (3), further condensation with o-phenylenediamine yields 2substituted benzimidazolyl 1H-isoindole-1,3(2H) diones (4), followed mannich reaction with methanal and different amines to yields final products (5). The chemical structures of synthesized N-Mannich bases were determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The class of isoindoline‐1,3‐diones has attracted much attention since it represents the core unit of a wide range of naturally‐occurring and bioactive substances . Literature survey revealed that some isoindoline‐1,3‐dione derivatives have antimicrobial , anthelmintic , insecticidal , antitubercular , anticonvulsant , anti‐inflammatory , and analgesic activities, besides their capability to inhibit cyclooxygenase and acetylcholinesterase . The pyrazolo[5,1‐ a ]isoindole derivatives were known to possess antihypotensive and antireproductive activities.…”
Section: Introductionmentioning
confidence: 99%
“…The class of isoindoline‐1,3‐diones has attracted much attention since it represents the core unit of a wide range of naturally‐occurring and bioactive substances . Literature survey revealed that some isoindoline‐1,3‐dione derivatives have antimicrobial , anthelmintic , insecticidal , antitubercular , anticonvulsant , anti‐inflammatory , and analgesic activities, besides their capability to inhibit cyclooxygenase and acetylcholinesterase . The pyrazolo[5,1‐ a ]isoindole derivatives were known to possess antihypotensive and antireproductive activities.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the phthalimide moiety is a very important biologically active pharmacophore . Antimicrobial properties of phthalimide derivatives were reported . Compounds IV and V (Figure ) exhibited high antimicrobial activities against the tested microorganisms .…”
Section: Introductionmentioning
confidence: 92%
“…It has been demonstrated that they are efficient against a number of different types of fungi [12], as well as inflammation and pain [13], convulsions [14], and bacteria [15], in addition to being antioxidants and hemolysers. N-Mannich bases of isoindolin-1,3-dione (phthalimide) and Mannich bases containing a phthalimide moiety have been discovered to be highly effective antibacterial, anthelmintic, and insecticidal agents [16,17]. These compounds are significant from a synthetic as biologically active compound.…”
Section: Introductionmentioning
confidence: 99%